The Attitudes of EFL Students towards Extensive Reading Program in Digital Library in Private Primary School (A Case of Erbil) - Ali Bala (International Journal of Social Sciences & Educational Studies, 2022)
Extensive Reading (ER) is described as an individual's voluntary and unrestricted reading of huge amounts of material or long texts for the sake of general comprehension and pleasure from the content. Digital libraries offer rich content and ample digital aids that student may get benefit while reading independently. These aids can help, encourage, and motivate children because of the digital additions that traditional books lack. They may be able to make reading books more entertaining for children by using bright animations and introducing them to print and pictures in an enjoyable way. Accordingly, the present research aims to examine the attitudes of private primary schools’ students towards an extensive reading program in digital library. A qualitative research methodology was selected to reveal the perceptions and preferences of the students. The collected data analysed through thematic analysis. The research participants are 10 students from grade 5 and 6 in a private primary school. This study might be useful for instructors to see how students react extensive reading program in digital library and technological features embedded to it, as well as curriculum designers to think about the impact of digital libraries on students' reading habit development.